IDENTIFYING FACTORS THAT AFFECT INDONESIA HOTEL INDUSTRY STOCK RETURN BY USING REGRESSION ANALYSIS - Panjaitan, Carlo Jeffry Emmanuel; Anggono, Achmad Herlanto (Journal of Business and Management, 2018)
Abstract. At present tourism is one of the pillars in economic development, based on world GDP in 2016 by 10.6% (based on World Travel & Tourism council) of world GDP. Due to the economic development due to tourism makes the entrepreneurs and investors start to invest in the world, but tingkast investment in tourism has not been evenly distributed, especially in Indonesia. From IDX shows that the stock price in the field of tourism hotels in Indonesia is still not good. In this journal mentioned what factors can be known by regression analysis. From this method found which factors that greatly affect the stock price of hospitality in Indonesia. This thesis elaborates the factor in the perspective Indonesia hotel industry stock market price. Using regression analysis consist which factor has affected the stock market price, the author tried to find the factor which has impact in stock market pricing. This thesis will found which factor has bigger impact, which can be improve by the government to attract more investor to develop Indoensia hotel tourism industry.Keywords : Hotel, Finance, Business, Risk and Return, Beta Analysis, Market, Travel, Tourism, Indonesia